Psychology Of An Anatomy: Comments To The Book Of Schydlowsky And Wicht - Schuldt, Jurgen (1980)
A few months after its appearance, the fifth edition of an exceptional book is in circulation: Anatomy of an economic failure: Peru, 1968-1978. The sales success has surprised its editors and probably also its authors, the Peruvian economists Daniel Schydlowsky and Juan Julio Wicht (1979). It is, therefore, a strange phenomenon in the national bookmarket, so depressed over the past five years. One explanation for this unexpected boom is undoubtedly due to the language so easy to boast and through which they sell a clear and basic message that promises to end all our problems in a short time and at minimal cost.